Antimicrobial Activities of Nisin, Tea Polyphenols, and Chitosan and their Combinations in Chilled Mutton. Issue 6 (20th April 2016) - He, Li; Zou, Likou; Yang, Qianru; Xia, Jinghua; Zhou, Kang; Zhu, Yuanting; Han, Xinfeng; Pu, Biao; Hu, Bin; Deng, Wenwen; Liu, Shuliang
Abstract: Antimicrobial activities of nisin, tea polyphenols (TPs), and chitosan, and their combinations were evaluated against both Gram‐positive bacteria (GPB) and Gram‐negative bacteria (GNB) by the agar dilution method. Results showed that the MIC of nisin was 2.44 to 1250 mg/L for GPB and reached 5000 mg/L for GNB. The MICs of TPs and chitosan were 313 to 625 mg/L and 469 mg/L for GNB, and 156 to 5000 mg/L and 234 to 938 mg/L for GPB, respectively. These results indicated that TPs and chitosan exhibited inhibitory effects against both GPB and GNB, whereas nisin inhibited the growth of GPB only. Based on the orthogonal test of their MICs, and evaluation of preservative effect and sensory attributes in chilled mutton, the optimum combination was chosen as 0.625, 0.313, and 3.752 g/L for nisin, TPs, and chitosan, respectively. By using the optimum treatment, the shelf life of chilled mutton was extended from 6 to 18 d at 4 °C in the preservative film packages. These results indicate that the combination of nisin, TPs, and chitosan could be used as preservatives to efficiently inhibit the growth of spoilage microorganisms and pathogens in meat, thus improving the safety and shelf life of chilled mutton.